2019
DOI: 10.1016/j.heliyon.2019.e03003
|View full text |Cite
|
Sign up to set email alerts
|

Adverse childhood experiences: prevalence and associated factors among South African young adults

Abstract: While adverse childhood experiences (ACEs), as described by the CDC-Kaiser Permanente Study, are reportedly common in both high and low-income settings, evidence on the epidemiology of ACEs in low-income settings is scarce. This study aimed to determine the prevalence of ACEs reported in young adulthood and assess their association with childhood maternal, household and community factors. We used data from the 22-23 year wave of the Birth to Twenty Plus (Bt20þ) study in South Africa, the largest and longest ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 48 publications
1
37
3
Order By: Relevance
“…Two studies of children and adolescents in Uganda found that depression was associated with loss of a parent and alcohol consumption [34] and domestic violence [35]. These and other studies have indicated a high prevalence of ACEs and associations with depression and suicidality among children, adolescents, and young adults in sub-Saharan Africa [31,32,36,37]. To address the gap in the literature on ACEs and mental health among adults, we aimed to estimate the associations between ACEs and depression symptom severity, major depressive disorder, and suicidal ideation in a population-based sample of adults in rural Uganda.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Two studies of children and adolescents in Uganda found that depression was associated with loss of a parent and alcohol consumption [34] and domestic violence [35]. These and other studies have indicated a high prevalence of ACEs and associations with depression and suicidality among children, adolescents, and young adults in sub-Saharan Africa [31,32,36,37]. To address the gap in the literature on ACEs and mental health among adults, we aimed to estimate the associations between ACEs and depression symptom severity, major depressive disorder, and suicidal ideation in a population-based sample of adults in rural Uganda.…”
Section: Introductionmentioning
confidence: 84%
“…While research studies from sub-Saharan Africa indicate a high prevalence of childhood adversity [29][30][31][32], research on the associations between ACEs and adult depression and suicidal ideation in these settings is limited. A study from South Africa found that emotional neglect and sexual abuse before age 18 were both associated with suicidality, problematic substance use, and depression 2 years after initial measurement among adolescents and young adults aged 15 to 26 [30].…”
Section: Introductionmentioning
confidence: 99%
“…Poverty is recognized as a significant barrier to children’s well-being, impacting on health and educational opportunities and increasing vulnerability to child maltreatment ( Fernandez, Delfabbro, Ramia, & Kovacs, 2019 ; Loffell, 2008 ; Manyema & Richter, 2019 ; Meinck, Cluver, & Boyes, 2015 ). Artz et al (2016) found that approximately 40% of young people in South Africa have had direct experiences of abuse.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Min et al found that children living in poverty were more likely to engage in sedentary behaviors and have a poor BMI growth trajectory than children of higher socioeconomic status [36]. Other recent studies have also reported a higher ACEs prevalence among children of lower socioeconomic status [37][38][39]. In addition, previous studies show that birth weight is an important predictor of childhood obesity and therefore could be a potential confounder [28,29].…”
Section: Plos Onementioning
confidence: 99%